Characterization and the influence of milk solids-not-fat on the bacteriocin produced by Lactococcus lactis subsp. lactis S20 isolated from Chinese sauerkraut, a traditional fermented vegetable - Yih, Zhet Chin; Velu, Selvi; Abu Bakar, Fatimah; Mahmud @ Ab Rashid, Nor Khaizura (Springer Verlag, 2016)
Lactococcus lactis subsp. lactis S20, a bacteriocinogenic lactic acid bacterium, was isolated from Chinese sauerkraut. This strain produced the highest bacteriocin activity (1280 AU/ml) against Listeria monocytogenes ATCC 19115 after 20 h of culture at 30 °C in MRS broth, although our results demonstrate that TSB was a suitable alternative bacteriocin production medium. Bacteriocin S20 exhibited inhibitory activity against most Gram-positive food pathogens but did not inhibit the growth of Gram-negative bacteria. Results of the stability tests indicate that bacteriocin S20 was resistant to trypsin, amylase, and lipase but sensitive to proteinase K, α-chymotrypsin, and pepsin. This bacteriocin was stable over a wide range of pH (pH 3–9) and at temperatures of up to 70 °C for 15 min. The bacteriocin activity of bacteriocin S20 dropped to 40 AU/ml after autoclaving at 121 °C for 15 min. Taken together, the results from the stability tests and molecular studies suggest that bacteriocin S20 is closely related to nisin A. Based on the bacteriocin adsorption study, pH 6 and pH 7 were the optimal pH for the adsorption of bacteriocin S20. The cells of the sensitive strain showed a higher adsorption of bacteriocin S20 than did the producer strain. However, adsorption to the resistant strain observed in this study suggests that bacteriocin S20 bound randomly to the cell membrane. Bacteriocin adsorption in the general medium TSB was relatively higher than that in MRS. Conversely, a higher recovery yield was observed in bacteriocin S20 extracted from MRS broth. In addition, bacteriocin S20 showed an effective antilisterial activity in skim milk containing <12 % (w/v) milk solids-not-fat.